Conjugated linoleic acid supplementation: Insights into prostaglandin synthesis and in vitro embryonic development - Maldonado, Mariângela Bueno Cordeiro [UNESP]; Cabrini, Dayane Colhados [UNESP]; de Oliveira Bezerra, Lucas [UNESP]; Rolniche, Laura Chuba Machado [UNESP]; de Castro Lourenço, Valeska [UNESP]; Feltrin, Isabella Rio [UNESP]; Morelli, Karine Galhego; Mendes, Adriano Felipe [UNESP]; Rocha, Cecilia Constantino; Bridi, Alessandra; Pugliesi, Guilherme; Nogueira, Marcelo Fábio Gouveia [UNESP]; et al. (Elsevier, 2025)
Modulation of prostaglandin synthesis, specifically, decreasing prostaglandin F2α (PGF2α) and increasing prostaglandin E2 (PGE2) and interferon-tau (IFNT), can support maternal recognition of pregnancy (MRP) in cattle. Conjugated linoleic acid (CLA) is known to influence prostaglandins (PG) synthesis in cell cultures; however, its effect on in vitro-cultured bovine oocytes and embryos remain unclear. We hypothesized that CLA supplementation in oocytes and embryo culture media would reduce PGF2α synthesis, increases PGE2 synthesis and PGE2:PGF2α ratio in embryos, modulate the expression of genes involved in PG and IFNT synthesis, and enhance embryo development. This study aimed to evaluate the effects of different CLA (a mixture of cis- and trans-9,11- and -10,12-octadecadienoic acids) concentrations (50-150 μM) added during in vitro maturation (IVM) and/or in vitro culture (IVC) on in vitro embryo production, PGE2 and PGF2α synthesis, and the expression of genes related to PG synthesis (AKR1B1, PTGS2, PTGES) and MPR (IFNT) in embryos. Oocytes and embryos were treated with CLA (50, 100, and 150 μM) during IVM or during both IVM and IVC. PGE2 and PGF2α concentrations were quantified by ELISA, and transcript abundance in embryos at the end of IVC was assessed by qPCR. CLA supplementation at all tested concentrations during IVM and/or IVC reduced both PGE2 and PGF2α synthesis in embryos, without affecting the PGE2:PGF2α ratio, or the relative expression of the evaluated genes. These findings suggest that CLA modulates PG synthesis in bovine embryos and underscore the importance of PG regulation for the successful establishment of MRP.